Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung (Studi Pada Objek Wisata Situ Cipanten Kabupaten Majalengka) - R. Neny Kusumadewi; Haris Fauzi; Kamelia Rosani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Tourist attractions have a crucial role in providing recreational and educational facilities for the community. The level of visitor satisfaction is greatly influenced by the availability of facilities and the quality of services provided. Situ Cipanten is one of the most popular tourist destinations because of its adequate facilities, such as a large parking area, clean toilets, easy digital payment systems, and a variety of recreational rides. In addition, its unique natural attractions, such as changes in water color according to the season, add to the charm of this place. This study aims to analyze the extent to which facilities and service quality affect visitor satisfaction. The approach used is a descriptive and verification method, with data collection through questionnaires distributed to 100 respondents selected using purposive sampling techniques. The data obtained were analyzed using the classical assumption test, multiple linear regression, coefficient of determination, and the F test and t test. The results of the study showed that facilities have a positive and significant effect on visitor satisfaction, as well as service quality which also has a positive and significant effect on visitor satisfaction.